INTERFERENSI GRAMATIKAL DALAM KUMPULAN CERPEN BIARKAN AKU MEMULAI KARYA NURUL F. HUDA - Liviana, Zimmatul (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2019)
The research grammatical interference in a collection ofshort stories Biarkan Aku Memula iwork Nurul F. Hudaisa collection ofshort storiesset in the back that Is start work Let Nurul F. Huda contains many grammatical interference.The problem of this study were(1)how the various morphologi calinterference containedin a collection of short stories Biarkan Aku Memulai work Nurul F. Huda. (2)how the various syntactic interference contained in a collection of short stories Biarkan Aku Memulai work Nurul F. Huda. The purposeof this studyis to describe the morphological and Syntactic interference contained in a collection of short stories Biarkan Aku Memulai work Nurul F. Huda. Sociolinguistics is the study of language variation and use in society. Interference is the event of the use of language elements of one into the other language elements that occur in the speakers themselves. This research uses descriptive qualitative method because to describe the actual realityin order to obtainan accurateand objective. Qualitative descriptive methods were used to analyzethe elements ofa word orphrase that incorporated elements of other languages with the analysis and description of the formulation of the problem is the answer. Data collection techniques using observation techniques, the determination ofthe object of research, the selection of short stories.Based on the analysis of the data in this study can be found that there are six forms of interference morphology, namely (1) the prefix nasal N-sound, (2) the addition of the suffix, (3) the exchange prefix, (4) exchange suffixes, (5) exchange konfiks, (6) removal affixes. While the syntactic interference only on the words and phrases in a sentence. The results of the study it can be concluded that the interference morphology more common than syntactic interference.